A water-soluble demulsifier and preparation method thereof

A water-soluble deemulsion agent was prepared by hydrothermal method, which was obtained by combining the carboxylated carbon nanotubes with molybdenum disulfide, and combined with modified block polymers and bis(trifluoromethylsulfonyl)imide anionic groups. The problem of poor deemulsion effect in the prior art under high temperature and high salt conditions was solved, and a high-efficiency and low-dose deemulsion effect was achieved.

CN119432426BActive Publication Date: 2025-04-18SHANDONG HUAYOU WANDA CHEMICAL CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510031257.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing water-soluble demulsification agents have poor demulsification effect under high temperature and high salt conditions, and are large in use and have a long time to demulsification.

Method used

Carboxylated carbon nanotubes were compounded with molybdenum disulfide by hydrothermal method, and a covalent bonded composite molybdenum disulfide was formed by alkali washing and quaternization reaction. Combined with a modified block polymer and a bis(trifluoromethylsulfonyl)imide anionic group, a water-soluble deemulsion agent was prepared.

Benefits of technology

Under high temperature and high salt conditions, water-soluble demulsifiers significantly improve the demulsification efficiency, reduce the dosage, and shorten the demulsification time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of oil extraction, and in particular to a water-soluble demulsifier and a preparation method thereof. The water-soluble demulsifier comprises the following raw materials in parts by weight: 10-12 parts of composite molybdenum disulfide and 80-90 parts of water. The composite molybdenum disulfide is used as a main demulsifying material, thereby solving the problems of large dosage, poor demulsification effect and long demulsification time of the existing water-soluble demulsifier, and at the same time, the water-soluble demulsifier can still maintain good demulsification performance under high temperature and high salt conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petroleum extraction, and in particular to a water-soluble demulsifier and a preparation method thereof. Background Art

[0002] In the process of oil extraction, water injection is usually used to improve the oil recovery rate. A large amount of oil-in-water emulsion or water-in-oil emulsion will be produced in the process of oil extraction, so it is necessary to demulsify them. The commonly used demulsification method is chemical demulsification. As the oil field production enters the later stage, the crude oil produced after tertiary oil recovery has a complex composition and its emulsion stability is getting higher and higher. The commonly used demulsifiers have the problems of large dosage, poor demulsification effect and long demulsification time. Therefore, a water-soluble demulsifier is needed that can still have good demulsification performance under complex conditions such as high temperature and high salt. Summary of the invention

[0003] The purpose of the present invention is to provide a water-soluble demulsifier and a preparation method thereof, which solves the problems of large dosage, poor demulsification effect and long demulsification time of existing water-soluble demulsifiers, and at the same time can still maintain good demulsification performance under high temperature and high salt conditions.

[0004] The object of the present invention can be achieved by the following technical scheme: A method for preparing a water-soluble demulsifier, comprising the following steps: weighing the following raw materials by weight: 10-12 parts of composite molybdenum disulfide and 80-90 parts of water, mixing the composite molybdenum disulfide and water to prepare a water-soluble demulsifier;

[0005] The composite molybdenum disulfide is prepared by the following steps:

[0006] Step A1: Carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide and deionized water are mixed and ultrasonically dispersed for 15-20 minutes, and reacted for 2-3 hours at a stirring rate of 100-120 rpm and a temperature of 40°C, and then sodium molybdate dihydrate, thioacetamide, glucose and polyvinyl pyrrolidone are added and mixed, and reacted for 20 hours at a temperature of 200°C, centrifuged, filtered, and washed to obtain precursor 1, and precursor 1 is mixed with deionized water and ultrasonically dispersed for 20 minutes, and stirred and sodium hydroxide solution is added at a stirring rate of 120-150 rpm and room temperature, and stirred for 6-8 hours, centrifuged, filtered, and washed, and then annealed for 3 hours at a heating rate of 5°C / min, nitrogen protection, and a temperature of 800°C to obtain precursor 2;

[0007] The amount ratio of carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide, sodium molybdate dihydrate, thioacetamide, glucose and polyvinylpyrrolidone is 0.02-0.022g: 0.01-0.012g: 0.3-0.32g: 0.3-0.32g: 0.1-0.11g: 0.25-0.3g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 1 and sodium hydroxide solution is 0.3-0.35g: 3-4mL;

[0008] During the reaction, hexadecyltrimethylammonium bromide is first grafted on the surface of the carboxylated carbon nanotube at a temperature of 40°C, and then a hydrothermal method is used at a temperature of 200°C to form molybdenum disulfide with sodium molybdate dihydrate and thioacetamide as molybdenum sources and sulfur sources, and the molybdenum disulfide is combined with the oxygen-containing functional groups on the surface of the carbon nanotube to form a covalent bond to obtain a precursor 1, and the precursor 1 is then alkaline washed with a sodium hydroxide solution. Since hexadecyltrimethylammonium bromide is grafted on the surface of the carboxylated carbon nanotube, defect sites appear in the molybdenum disulfide nanosheet after alkaline washing, and then it is calcined to obtain a precursor 2;

[0009] Step A2: Precursor 2 and isopropanol were mixed and ultrasonically dispersed for 15-20 minutes, and 1-methyl-2-mercaptoimidazole was added under stirring at a rate of 150-180 rpm and room temperature, and the mixture was reacted for 3-4 hours to obtain Precursor 3. Precursor 3, modified block polymer and tetrahydrofuran were mixed, and the mixture was reacted for 12 hours under stirring at a rate of 120-150 rpm and a temperature of 70° C. to obtain Precursor 4;

[0010] The amount ratio of precursor 2, isopropanol and 1-methyl-2-mercaptoimidazole is 0.24-0.26 g: 60-65 mL: 0.01-0.012 mol; the amount ratio of precursor 3, modified block polymer and tetrahydrofuran is 1.6-1.75 g: 0.85-0.9 g: 50-60 mL;

[0011] During the reaction, the mercapto group in 1-methyl-2-mercaptoimidazole combines with the defect point of molybdenum disulfide in precursor 2 to obtain precursor 3. The imidazole group in precursor 3 then reacts with the chlorine in the modified block polymer to form an imidazolium structure to obtain precursor 4.

[0012] Step A3: Precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water are mixed, and the mixture is reacted for 3-4 hours at a stirring rate of 300-400 rpm and a temperature of 40° C. to obtain composite molybdenum disulfide;

[0013] The ratio of precursor 4, bis(trifluoromethylsulfonyl)imide zinc and deionized water is 6-6.5 g: 10-11 g: 120-140 mL;

[0014] During the reaction, bis(trifluoromethylsulfonyl)imide zinc undergoes an ion exchange reaction with the imidazolium salt structure in the precursor 4, introducing a bis(trifluoromethylsulfonyl)imide anion group to prepare a composite molybdenum disulfide.

[0015] The modified block polymer is prepared by the following steps:

[0016] Step B1: dimethyldichlorosilane, methyldichlorosilane, xylene, acetone and deionized water are mixed, and the mixture is reacted for 2-2.5 hours at a stirring rate of 60-80 rpm and a temperature of 60° C., and then 3-aminopropyldimethoxymethylsilane and isopropanol are added and mixed, and the mixture is reacted for 6-8 hours at a stirring rate of 150-180 rpm and a temperature of 110° C. to obtain a modified hydrogenated silicone oil;

[0017] The dosage ratio of dimethyldichlorosilane, methyldichlorosilane, xylene, acetone, deionized water and 3-aminopropyldimethoxymethylsilane is 0.04-0.05mol: 0.045-0.055mol: 80-100mL: 60-80mL: 40-50mL: 0.01-0.012mol;

[0018] During the reaction, dimethyldichlorosilane and methyldichlorosilane are hydrolyzed and copolymerized in water to form a linear structure, which is then terminated by reaction with 3-aminopropyldimethoxymethylsilane under the action of isopropanol to obtain a modified hydrogenated silicone oil.

[0019] Step B2: mixing double-terminal epoxy polyether, modified hydrogen-containing silicone oil, isopropanol and acetone, reacting for 4-6 hours under nitrogen protection, stirring at a rate of 300-350 rpm and a temperature of 80° C. to obtain a block polymer; mixing the block polymer, 4-chloromethylstyrene and Custer catalyst, reacting for 4-5 hours under a stirring rate of 160-180 rpm and a temperature of 90° C. to obtain a modified block polymer;

[0020] The ratio of double-terminal epoxy polyether, modified hydrogen-containing silicone oil and isopropanol is 6-8g: 5.5-6g: 8-10mL; block polymer, 4-chloromethylstyrene and Custer catalyst is 4-5g: 0.0015-0.002mol: 0.15-0.2g;

[0021] During the reaction, the epoxy groups in the double-terminal epoxy polyether react with the amino groups in the modified hydrogen-containing silicone oil to obtain a block polymer, and then under the action of the Custer catalyst, the double bonds in 4-chloromethylstyrene react with the block polymer to undergo a hydrosilylation reaction to obtain a modified block polymer.

[0022] Beneficial effects of the invention: The invention discloses a water-soluble demulsifier and a preparation method thereof, which solves the problems of large dosage, poor demulsification effect and long demulsification time of the existing water-soluble demulsifier, and at the same time, it can still maintain good demulsification performance under high temperature and high salt conditions; the main component of the water-soluble demulsifier is composite molybdenum disulfide, and the carboxylated carbon nanotubes are modified by a hydrothermal method and then composited with molybdenum disulfide and alkali-washed in the process, so that the molybdenum disulfide and the carboxylated carbon nanotubes are connected by covalent bonds, and at the same time, the defective sites react with 1-methyl-2-thioimidazole, and then composited with the modified block polymer by a quaternization reaction, and then introduced by an ion exchange reaction. The composite molybdenum disulfide is prepared by the (trifluoromethylsulfonyl)imide anion group. In the emulsion system of crude oil produced fluid, due to the special structure of the carboxylated carbon nanotubes themselves and their π-π interaction, it can show a good demulsification effect under high temperature and high salt conditions. At the same time, due to its modified block polymer with silicon oxygen segments and polyether segments, it can also show a good demulsification effect. The bis (trifluoromethylsulfonyl)imide anion group introduced by it is gradually released and diffused during the diffusion process of the demulsifier, and is adsorbed on the interface by hydrogen bonding or osmotic action, thereby changing the viscoelastic properties of the interface, and then showing a better demulsification efficiency. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 A method for preparing a water-soluble demulsifier comprises the following steps: weighing the following raw materials in parts by weight: 10 parts of composite molybdenum disulfide and 90 parts of water, mixing the composite molybdenum disulfide and water to prepare a water-soluble demulsifier;

[0025] The composite molybdenum disulfide is prepared by the following steps:

[0026] Step A1: Mix commercially available Yuechuang carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide and deionized water and ultrasonically disperse them for 15 minutes, react for 2 hours at a stirring rate of 100 rpm and a temperature of 40°C, then add sodium molybdate dihydrate, thioacetamide, glucose and polyvinyl pyrrolidone and mix, react for 20 hours at a temperature of 200°C, centrifuge, filter, and wash to obtain precursor 1, mix precursor 1 and deionized water and ultrasonically disperse them for 20 minutes, stir and add sodium hydroxide solution at a stirring rate of 120 rpm and room temperature, stir for 6 hours, centrifuge, filter, wash, and then anneal for 3 hours at a heating rate of 5°C / min, nitrogen protection, and a temperature of 800°C to obtain precursor 2;

[0027] The amount ratio of carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide, sodium molybdate dihydrate, thioacetamide, glucose and polyvinylpyrrolidone is 0.02g: 0.01g: 0.3g: 0.3g: 0.1g: 0.25g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 1 and sodium hydroxide solution is 0.3g: 3mL;

[0028] Step A2: Precursor 2 and isopropanol were mixed and ultrasonically dispersed for 15 minutes, and 1-methyl-2-mercaptoimidazole was added under stirring at a rate of 150 rpm and room temperature, and the mixture was reacted for 3 hours to obtain Precursor 3. Precursor 3, modified block polymer and tetrahydrofuran were mixed, and the mixture was reacted for 12 hours under stirring at a rate of 120 rpm and a temperature of 70° C. to obtain Precursor 4;

[0029] The amount ratio of precursor 2, isopropanol and 1-methyl-2-mercaptoimidazole is 0.24 g: 60 mL: 0.01 mol; the amount ratio of precursor 3, modified block polymer and tetrahydrofuran is 1.6 g: 0.85 g: 50 mL;

[0030] Step A3: Precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water were mixed, and the mixture was reacted for 3 h at a stirring rate of 300 rpm and a temperature of 40° C. to obtain composite molybdenum disulfide;

[0031] The amount ratio of precursor 4, bis(trifluoromethylsulfonyl)imide zinc and deionized water is 6 g:10 g:120 mL;

[0032] The modified block polymer is prepared by the following steps:

[0033] Step B1: dimethyldichlorosilane, methyldichlorosilane, xylene, acetone and deionized water were mixed, and the mixture was reacted for 2 h at a stirring rate of 60 rpm and a temperature of 60° C., and then 3-aminopropyldimethoxymethylsilane and isopropanol were added and mixed, and the mixture was reacted for 6 h at a stirring rate of 150 rpm and a temperature of 110° C. to obtain a modified hydrogenated silicone oil;

[0034] The ratio of dimethyldichlorosilane, methyldichlorosilane, xylene, acetone, deionized water and 3-aminopropyldimethoxymethylsilane is 0.04mol:0.045mol:80mL:60mL:40mL:0.01mol;

[0035] Step B2: Mix commercially available Kermik double-terminal epoxy polyether, modified hydrogen-containing silicone oil, isopropanol and acetone, and react for 4 hours under nitrogen protection, stirring at a rate of 300 rpm and a temperature of 80°C to obtain a block polymer; mix the block polymer, 4-chloromethylstyrene and Custer catalyst, and react for 4 hours under a stirring rate of 160 rpm and a temperature of 90°C to obtain a modified block polymer;

[0036] The dosage ratio of double-terminal epoxy polyether, modified hydrogen-containing silicone oil and isopropanol is 6g:5.5g:8mL; the dosage ratio of block polymer, 4-chloromethylstyrene and Custer catalyst is 4g:0.0015mol:0.15g.

[0037] Example 2 A method for preparing a water-soluble demulsifier comprises the following steps: weighing the following raw materials in parts by weight: 12 parts of composite molybdenum disulfide and 80 parts of water, mixing the composite molybdenum disulfide and water to prepare a water-soluble demulsifier;

[0038] The composite molybdenum disulfide is prepared by the following steps:

[0039] Step A1: Mix commercially available Yuechuang carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide and deionized water and ultrasonically disperse for 15 minutes, react for 3 hours at a stirring rate of 120 rpm and a temperature of 40°C, then add sodium molybdate dihydrate, thioacetamide, glucose and polyvinyl pyrrolidone and mix, react for 20 hours at a temperature of 200°C, centrifuge, filter, and wash to obtain precursor 1, mix precursor 1 and deionized water and ultrasonically disperse for 20 minutes, stir and add sodium hydroxide solution at a stirring rate of 120 rpm and room temperature, stir for 8 hours, centrifuge, filter, wash, and then anneal for 3 hours at a heating rate of 5°C / min, nitrogen protection, and a temperature of 800°C to obtain precursor 2;

[0040] The amount ratio of carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide, sodium molybdate dihydrate, thioacetamide, glucose and polyvinylpyrrolidone is 0.022g: 0.01g: 0.32g: 0.32g: 0.1g: 0.3g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 1 and sodium hydroxide solution is 0.35g: 3mL;

[0041] Step A2: Precursor 2 and isopropanol were mixed and ultrasonically dispersed for 20 minutes, and 1-methyl-2-mercaptoimidazole was added under stirring at a rate of 150 rpm and room temperature, and the mixture was reacted for 4 hours to obtain Precursor 3. Precursor 3, modified block polymer and tetrahydrofuran were mixed, and the mixture was reacted for 12 hours under stirring at a rate of 150 rpm and a temperature of 70° C. to obtain Precursor 4;

[0042] The amount ratio of precursor 2, isopropanol and 1-methyl-2-mercaptoimidazole is 0.24 g: 65 mL: 0.01 mol; the amount ratio of precursor 3, modified block polymer and tetrahydrofuran is 1.6 g: 0.9 g: 60 mL;

[0043] Step A3: Precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water were mixed, and the mixture was reacted for 4 h at a stirring rate of 300 rpm and a temperature of 40° C. to obtain composite molybdenum disulfide;

[0044] The amount ratio of precursor 4, bis(trifluoromethylsulfonyl)imide zinc and deionized water is 6 g:11 g:120 mL;

[0045] The modified block polymer is prepared by the following steps:

[0046] Step B1: dimethyldichlorosilane, methyldichlorosilane, xylene, acetone and deionized water were mixed, and the mixture was reacted for 2 h at a stirring rate of 80 rpm and a temperature of 60° C., and then 3-aminopropyldimethoxymethylsilane and isopropanol were added and mixed, and the mixture was reacted for 6 h at a stirring rate of 180 rpm and a temperature of 110° C. to obtain a modified hydrogenated silicone oil;

[0047] The usage ratio of dimethyldichlorosilane, methyldichlorosilane, xylene, acetone, deionized water and 3-aminopropyldimethoxymethylsilane is 0.05mol:0.045mol:100mL:60mL:50mL:0.012mol;

[0048] Step B2: Mix commercially available Kermik double-terminal epoxy polyether, modified hydrogen-containing silicone oil, isopropanol and acetone, and react for 6 hours under nitrogen protection, stirring at a rate of 300 rpm and a temperature of 80°C to obtain a block polymer; mix the block polymer, 4-chloromethylstyrene and Custer catalyst, and react for 5 hours under a stirring rate of 160 rpm and a temperature of 90°C to obtain a modified block polymer;

[0049] The dosage ratio of double-ended epoxy polyether, modified hydrogen-containing silicone oil and isopropanol is 6g:6g:8mL; the dosage ratio of block polymer, 4-chloromethylstyrene and Custer catalyst is 4g:0.002mol:0.2g.

[0050] Example 3 A method for preparing a water-soluble demulsifier comprises the following steps: weighing the following raw materials in parts by weight: 12 parts of composite molybdenum disulfide and 90 parts of water, mixing the composite molybdenum disulfide and water to prepare a water-soluble demulsifier;

[0051] The composite molybdenum disulfide is prepared by the following steps:

[0052] Step A1: Mix commercially available Yuechuang carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide and deionized water and ultrasonically disperse for 20 minutes, react for 3 hours at a stirring rate of 120 rpm and a temperature of 40°C, then add sodium molybdate dihydrate, thioacetamide, glucose and polyvinyl pyrrolidone and mix, react for 20 hours at a temperature of 200°C, centrifuge, filter, and wash to obtain precursor 1, mix precursor 1 and deionized water and ultrasonically disperse for 20 minutes, stir and add sodium hydroxide solution at a stirring rate of 150 rpm and room temperature, stir for 8 hours, centrifuge, filter, wash, and then anneal for 3 hours at a heating rate of 5°C / min, nitrogen protection, and a temperature of 800°C to obtain precursor 2;

[0053] The amount ratio of carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide, sodium molybdate dihydrate, thioacetamide, glucose and polyvinylpyrrolidone is 0.022g: 0.012g: 0.32g: 0.32g: 0.11g: 0.3g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 1 and sodium hydroxide solution is 0.35g: 4mL;

[0054] Step A2: Precursor 2 and isopropanol were mixed and ultrasonically dispersed for 20 minutes, and 1-methyl-2-mercaptoimidazole was added under stirring at a rate of 180 rpm and room temperature, and the mixture was reacted for 4 hours to obtain Precursor 3. Precursor 3, modified block polymer and tetrahydrofuran were mixed, and the mixture was reacted for 12 hours under stirring at a rate of 150 rpm and a temperature of 70° C. to obtain Precursor 4;

[0055] The amount ratio of precursor 2, isopropanol and 1-methyl-2-mercaptoimidazole is 0.26 g: 65 mL: 0.012 mol; the amount ratio of precursor 3, modified block polymer and tetrahydrofuran is 1.75 g: 0.9 g: 60 mL;

[0056] Step A3: Precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water were mixed, and the mixture was reacted for 4 h at a stirring rate of 400 rpm and a temperature of 40° C. to obtain composite molybdenum disulfide;

[0057] The amount ratio of precursor 4, bis(trifluoromethylsulfonyl)imide zinc and deionized water is 6.5 g:11 g:140 mL;

[0058] The modified block polymer is prepared by the following steps:

[0059] Step B1: dimethyldichlorosilane, methyldichlorosilane, xylene, acetone and deionized water were mixed, and the mixture was reacted for 2.5 hours at a stirring rate of 80 rpm and a temperature of 60° C., and then 3-aminopropyldimethoxymethylsilane and isopropanol were added and mixed, and the mixture was reacted for 8 hours at a stirring rate of 180 rpm and a temperature of 110° C. to obtain a modified hydrogenated silicone oil;

[0060] The dosage ratio of dimethyldichlorosilane, methyldichlorosilane, xylene, acetone, deionized water and 3-aminopropyldimethoxymethylsilane is 0.05mol:0.055mol:100mL:80mL:50mL:0.012mol;

[0061] Step B2: Mix commercially available Kermik double-terminal epoxy polyether, modified hydrogen-containing silicone oil, isopropanol and acetone, and react for 6 hours under nitrogen protection, stirring at a rate of 350 rpm and a temperature of 80°C to obtain a block polymer; mix the block polymer, 4-chloromethylstyrene and Custer catalyst, and react for 5 hours under a stirring rate of 180 rpm and a temperature of 90°C to obtain a modified block polymer;

[0062] The dosage ratio of double-terminal epoxy polyether, modified hydrogen-containing silicone oil and isopropanol is 8g:6g:10mL; the dosage ratio of block polymer, 4-chloromethylstyrene and Custer catalyst is 5g:0.002mol:0.2g.

[0063] Comparative Example 1 Compared with Example 3, this comparative example is different in that the block polymer in the preparation process of the modified block polymer in Example 3 is replaced with commercially available Shengbang SI-H202 hydrogen-containing silicone oil, and the other steps are the same.

[0064] Comparative Example 2 Compared with Example 3, this comparative example is to remove zinc bis(trifluoromethylsulfonyl)imide in the preparation process of composite molybdenum disulfide in Example 3, and the other steps are the same.

[0065] Comparative Example 3 Compared with Example 3, this comparative example replaces the commercially available Yuechuang carboxylated carbon nanotubes in the preparation process of the modified block polymer in Example 3 with commercially available Yuechuang carbon nanotubes, and the other steps are the same.

[0066] Take a water-soluble demulsifier prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, mix ammonium ferrous sulfate, sodium sulfide solution and deionized water to prepare a 100 mg / kg ferrous sulfide solution, mix the Tahe Oilfield crude oil sample, commercially available 1250 mesh quartz sand, ferrous sulfate solution and water, adjust the pH value to 6, emulsify for 5 minutes at a stirring rate of 28000 rpm to prepare an emulsion system, wherein the mass percentage of crude oil is 0.5%, The amount of ferrous sulfide and quartz sand added was 100 mg / kg, and the water-soluble demulsifier was mixed with the emulsion system. The amount of water-soluble demulsifier was 50 mg / L. At the temperature of 40°C and 60°C, it was vibrated up and down 100 times and kept warm for 2 hours. The dehydration rate was calculated. Then, the dehydration rate was calculated at a pH value of 4 and a temperature of 40°C. Then, the dehydration rate was calculated at a pH value of 6, an amount of ferrous sulfide added of 180 mg / kg, and a temperature of 40°C. The test results are shown in Table 1 below:

[0067] Table 1 Test results

[0068]

[0069] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, the block polymer in the preparation process of the modified block polymer in Example 3 is replaced by the commercially available Shengbang SI-H202 hydrogen-containing silicone oil. Due to the lack of block structure, its performance is reduced. In Comparative Example 2, the zinc bis(trifluoromethylsulfonyl)imide is removed in the preparation process of the composite molybdenum disulfide in Example 3. Due to the lack of anionic groups, its performance is reduced. In Comparative Example 3, the commercially available Yuechuang carboxylated carbon nanotubes in the preparation process of the modified block polymer in Example 3 are replaced by commercially available Yuechuang carbon nanotubes. Due to the lack of carbon nanotube composite, its performance is reduced.

[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0071] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a water-soluble demulsifier, characterized in that: The method comprises the following steps: weighing the following raw materials by weight: 10-12 parts of composite molybdenum disulfide and 80-90 parts of water, mixing the composite molybdenum disulfide and water to prepare a water-soluble demulsifier; The composite molybdenum disulfide is prepared by the following steps: Step A1: Carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide and deionized water are mixed and ultrasonically dispersed for 15-20 minutes, and reacted for 2-3 hours at a stirring rate of 100-120 rpm and a temperature of 40°C, and then sodium molybdate dihydrate, thioacetamide, glucose and polyvinyl pyrrolidone are added and mixed, and reacted for 20 hours at a temperature of 200°C, centrifuged, filtered, and washed to obtain precursor 1, and precursor 1 is mixed with deionized water and ultrasonically dispersed for 20 minutes, and stirred and sodium hydroxide solution is added at a stirring rate of 120-150 rpm and room temperature, and stirred for 6-8 hours, centrifuged, filtered, and washed, and then annealed for 3 hours at a heating rate of 5°C / min, nitrogen protection, and a temperature of 800°C to obtain precursor 2; Step A2: Precursor 2 and isopropanol were mixed and ultrasonically dispersed for 15-20 minutes, and 1-methyl-2-mercaptoimidazole was added under stirring at a rate of 150-180 rpm and room temperature, and the mixture was reacted for 3-4 hours to obtain Precursor 3. Precursor 3, modified block polymer and tetrahydrofuran were mixed, and the mixture was reacted for 12 hours under stirring at a rate of 120-150 rpm and a temperature of 70° C. to obtain Precursor 4; Step A3: Precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water are mixed, and the mixture is reacted for 3-4 hours at a stirring rate of 300-400 rpm and a temperature of 40° C. to obtain composite molybdenum disulfide; The modified block polymer is prepared by the following steps: Step B1: dimethyldichlorosilane, methyldichlorosilane, xylene, acetone and deionized water are mixed, and the mixture is reacted for 2-2.5 hours at a stirring rate of 60-80 rpm and a temperature of 60° C., and then 3-aminopropyldimethoxymethylsilane and isopropanol are added and mixed, and the mixture is reacted for 6-8 hours at a stirring rate of 150-180 rpm and a temperature of 110° C. to obtain a modified hydrogenated silicone oil; Step B2: Mix double-ended epoxy polyether, modified hydrogenated silicone oil, isopropanol and acetone, and react for 4-6 hours under nitrogen protection, stirring at a rate of 300-350 rpm and a temperature of 80°C to obtain a block polymer; mix the block polymer, 4-chloromethylstyrene and Custer catalyst, and react for 4-5 hours under a stirring rate of 160-180 rpm and a temperature of 90°C to obtain a modified block polymer.

2. The method for preparing a water-soluble demulsifier according to claim 1, characterized in that: In step A1: the amount ratio of carboxylated carbon nanotubes, hexadecyltrimethylammonium bromide, sodium molybdate dihydrate, thioacetamide, glucose and polyvinylpyrrolidone is 0.02-0.022g: 0.01-0.012g: 0.3-0.32g: 0.3-0.32g: 0.1-0.11g: 0.25-0.3g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 1 and sodium hydroxide solution is 0.3-0.35g: 3-4mL.

3. The method for preparing a water-soluble demulsifier according to claim 1, characterized in that: In step A2: the amount ratio of precursor 2, isopropanol and 1-methyl-2-mercaptoimidazole is 0.24-0.26 g: 60-65 mL: 0.01-0.012 mol; the amount ratio of precursor 3, modified block polymer and tetrahydrofuran is 1.6-1.75 g: 0.85-0.9 g: 50-60 mL.

4. The method for preparing a water-soluble demulsifier according to claim 1, characterized in that: In step A3: the ratio of the precursor 4, zinc bis(trifluoromethylsulfonyl)imide and deionized water is 6-6.5 g: 10-11 g: 120-140 mL.

5. The method for preparing a water-soluble demulsifier according to claim 1, characterized in that: In step B1, the usage ratio of dimethyldichlorosilane, methyldichlorosilane, xylene, acetone, deionized water and 3-aminopropyldimethoxymethylsilane is 0.04-0.05 mol: 0.045-0.055 mol: 80-100 mL: 60-80 mL: 40-50 mL: 0.01-0.012 mol.

6. The method for preparing a water-soluble demulsifier according to claim 1, characterized in that: In step B2: the ratio of double-ended epoxy polyether, modified hydrogen-containing silicone oil and isopropanol is 6-8g: 5.5-6g: 8-10mL; block polymer, 4-chloromethylstyrene and Custer catalyst 4-5g: 0.0015-0.002mol: 0.15-0.2g.

7. A water-soluble demulsifier, characterized in that: Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Compositions and methods for separating fluids

    CN107427838A

  • Nanoformulations and functionalized polymers for iron removal from crude oil

    US11667851B1